A Comparative Study of Phase Offset Disposition Sinusoidal Pulse Width Modulation (POD-SPWM) and Symmetrical Pulse Width Modulation Switching Techiques for Generalized Current Source Multilevel Inverter(MCSI) - Nik Fasdi Nik Ismail; Nasrudin Abdul Rahim; Siti Rohani Sheikh Raihan; Yusuf Al-Turki (Indonesian Journal of Electrical Engineering and Computer Science, 2018)
This paper presents a comparison between two switching techniques namely Phase Offset Disposition Sinusoidal PWM (POD-SPWM) and Symmetrical PWM switching for a generalized current source multilevel inverter (MCSI) topology. One of the advantages of MCSI is it can reduce the total harmonic distortion (THD) at the output load current with a sinusoidal current waveform. In this paper, the generalized MCSI with the different levels has been developed with Matlab@simulation software in order to study the performance of the two switching schemes for the operation of the MCSI. From the simulation results, POD-SPWM switching technique can give better THD results compare to symmetrical switching technique.